Rare complication of ganglion impar blockade with the transsacrococcygeal approach: A case of rectal perforation - OKÇU, MEHMET; ŞENCAN, SAVAŞ; GÜNDÜZ, OSMAN HAKAN (My University, 2022)
Although it has been reported that caution should be exercised in terms of rectal perforation, as the ganglion impar is located just behind the rectum in the presacral space, the authors could not find any case or images of rectal perforation occurring during ganglion impar blockade in the literature. In this report, the case of a 38-year-old female with rectal perforation that developed during ganglion impar blockade, performed by the transsacrococcygeal approach under fluoroscopy guidance, is presented. Wrong needle selection and the structurally short presacral space of the patient may have influenced the development of rectal perforation in the patient. This study presents the first case and images of rectal perforation in the literature that developed during the application of ganglion impar blockade using the transsacrococcygeal technique. In ganglion impar block applications, technically appropriate needles should be used, and care should be taken in terms of rectal perforation.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Coccygodynia; ganglion impar blockade; rectal perforation; rectum perforation; transsacrococcygeal approach; Coccygodynia; ganglion impar blockade; rectal perforation; rectum perforation; transsacrococcygeal approach.